High ratio of programmed cell death protein 1 (PD-1)+/CD8+ tumor-infiltrating lymphocytes identifies a poor prognostic subset of extrahepatic bile duct cancer undergoing surgery plus adjuvant chemoradiotherapy. Issue 1 (October 2015) - Lim, Yu Jin; Koh, Jaemoon; Kim, Kyubo; Chie, Eui Kyu; Kim, BoKyong; Lee, Kyoung Bun; Jang, Jin-Young; Kim, Sun-Whe; Oh, Do-Youn; Bang, Yung-Jue; Ha, Sung W.
Abstract Background and purpose This study investigated the prognostic role of PD-L1 expression, PD-1+ tumor-infiltrating lymphocytes (TILs), and the ratio of PD-1+/CD8+ TILs in extrahepatic bile duct (EHBD) cancer. Materials and methods We analyzed 83 patients with EHBD cancer who underwent curative surgery plus fluoropyrimidine-based chemoradiotherapy (CRT). Expressions of PD-L1, PD-1, and CD8 were assessed by immunohistochemistry. Results Fifty-six (68%) patients were PD-L1-positive, and its lower expression level was associated with hilar tumor location (P = 0.044). A higher ratio of PD-1+/CD8+ TILs was associated with poorer overall survival (OS) (P = 0.032), relapse-free survival (RFS) (P = 0.024), and distant metastasis-free survival (DMFS) (P = 0.039) in Kaplan–Meier analyses, but survival differences were not observed according to the PD-L1 expression level. With Cox proportional hazards models, the ratio of PD-1+/CD8+ TILs was the independent prognostic factor in OS (HR 2.47, 95% CI 1.04–5.86), RFS (HR 2.41, 95% CI 1.08–5.41), and DMFS (HR 2.67, 95% CI 1.00–7.11) after adjusting for other significant clinicopathologic variables. Conclusion A strong survival impact of the ratio of PD-1+/CD8+ TILs was observed in EHBD cancer. In the poor prognostic subgroup, the blockade of the immune checkpoint in combination with conventional multimodality treatment needs to be considered.